Enhancing Critical Thinking Skills through the Guided Inquiry Learning Model in Science Education - Nurhalisa; Arda; Rahmawaty (Program Studi Tadris Matematika dan Tadris Ilmu Pengetahuan Alam, Fakultas Tarbiyah dan Ilmu Keguruan (FTIK), Universitas Islam Negeri (UIN) Datokarama Palu, 2025)
This study investigates the enhancement of students’ critical thinking skills through the implementation of the guided inquiry learning model in science instruction of eighth-grade students at MTs Negeri 2 Kota Palu. Employing quasi-experimental with nonequivalent pretest-posttest control group design, the study involved two classes: an experimental group receiving instruction via the guided inquiry model, and a control group taught using conventional model. Data were gathered through a 15-item critical thinking skills test, validated for both reliability and validity. Prior to hypothesis testing, assumptions of normality and homogeneity were confirmed. Students in the experimental group significantly improved their critical thinking abilities when compared to the control group, according to further analysis using an independent samples t-test. These results imply that critical thinking skills are successfully enhanced in science education through used of the guided inquiry learning model.